The Influence of Celebrity Endorsements towards Purchase Intention, Mediated by Brand Image: the case of Nike and Travis Scott - Rachel D. Moeliadji; Reagan K. P. Halim (iBuss Management, 2023)
Nike, an old player that has ruled the athletic footwear and apparel industry recently just dropped a bombshell news. The world is staggered by Nike’s interesting decision by choosing Travis Scott, an American rapper, as their celebrity endorsement. Given this phenomenon, we analyzed the relationship between celebrity endorsement, brand image, and purchase intention if implemented through a cross-industry endorsement strategy. We analyzed the phenomenon utilizing the theory of purchase intention and celebrity endorsement, with the brand image as a mediating variable. The research utilizes simple random sampling through a close-ended questionnaire distributed on social media as our method to collect data. Further, the data will be analyzed through PLS-SEM method by using SMART PLS 4 software. The result of the research shows that celebrity endorsement results in a positive impact on customers' purchase intention and the company's brand image. With the increasing value of Nike's brand image, brand image has a positive mediation impact on the relationship between celebrity endorsement and purchase intention. This research enriches the theory of purchase intention, brand image, and celebrity endorsement, providing a cross-industry element in an intersecting branding strategy for a wider market to conduct a purchase. With further enrichment of the theory, this research enlarges the space for innovation in the marketing and creative industry.Keywords: Nike, branding, influence, celebrity endorsement, customer purchase intention, random sampling.